The Sheep and Goat Sector in Romania: Economic Perspectives and Development Directions - Adrian Petre Liptac; Silvius Stanciu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
Sheep and goat farming is an important activity for farmers in Romania. This paper proposes an analysis of the economic perspectives and development directions of the sector, highlighting its traditional importance and significant contribution to the rural economy. The research results highlight Romania's leading position in European live sheep exports, primarily determined by strong partnerships with countries in the Middle East. The analysis includes historical trends, market dynamics, and trade practices, along with challenges such as market concentration and dependence on external partners. The conclusions emphasize the need for geographical diversification of exports, the development of the processing sector, and political support to stabilize production and maximize economic benefits for Romanian farmers.